2021
DOI: 10.1093/jcbiol/ruab038
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern in Aegla uruguayana Schmitt, 1942 (Decapoda: Anomura: Aeglidae): temporal and spatial approach

Abstract: The presence, density, and distribution pattern of a species in a particular space and time result from evolutionary and ecological processes. We evaluated the density and spatial distribution pattern of the freshwater anomuran crab, Aegla uruguayanaSchmitt, 1942, in relation to temporal and spatial scales. The temporal scale followed a seasonal analysis, and the space scale was evaluated from the study of three streams located in different provinces of Argentina. Specimens were collected in four sampling camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results about spatial distribution of inland water crustaceans revealed the existence of aggregated spatial distribution (De los Ríos-Escalante et al 2011; De los Ríos-Escalante and Mancilla 2017; De los Ríos-Escalante, 2017; Diawol, Musin, Collins, Giri, 2021), that is a very frequent pattern of inland water benthic invertebrates (Elliot, 1975;Gray, 2005). Although the statistical literature described that aggregated distribution implies negative binomial distribution pattern (Zar, 1999), that is supported by statistical ecological references (Fernandes et al 2003;Diawol et al, 2021), it is not obligatory situation (Elliot, 1975), that was observed on the basis of field evidences (De los Ríos-Escalante et al, 2011;De los Ríos-Escalante and Mancilla, 2017), the cause of the absence of associations between negative binomial distribution and aggregated pattern is due probably to complex ecological process, such as environmental heterogeneity (Elliot, 1975;Benton, Lapsley, Beckerman, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results about spatial distribution of inland water crustaceans revealed the existence of aggregated spatial distribution (De los Ríos-Escalante et al 2011; De los Ríos-Escalante and Mancilla 2017; De los Ríos-Escalante, 2017; Diawol, Musin, Collins, Giri, 2021), that is a very frequent pattern of inland water benthic invertebrates (Elliot, 1975;Gray, 2005). Although the statistical literature described that aggregated distribution implies negative binomial distribution pattern (Zar, 1999), that is supported by statistical ecological references (Fernandes et al 2003;Diawol et al, 2021), it is not obligatory situation (Elliot, 1975), that was observed on the basis of field evidences (De los Ríos-Escalante et al, 2011;De los Ríos-Escalante and Mancilla, 2017), the cause of the absence of associations between negative binomial distribution and aggregated pattern is due probably to complex ecological process, such as environmental heterogeneity (Elliot, 1975;Benton, Lapsley, Beckerman, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The results about spatial distribution of inland water crustaceans revealed the existence of aggregated spatial distribution (De los Ríos-Escalante et al 2011; De los Ríos-Escalante and Mancilla 2017; De los Ríos-Escalante, 2017; Diawol, Musin, Collins, Giri, 2021), that is a very frequent pattern of inland water benthic invertebrates (Elliot, 1975;Gray, 2005). Although the statistical literature described that aggregated distribution implies negative binomial distribution pattern (Zar, 1999), that is supported by statistical ecological references (Fernandes et al 2003;Diawol et al, 2021), it is not obligatory situation (Elliot, 1975), that was observed on the basis of field evidences (De los Ríos-Escalante et al, 2011;De los Ríos-Escalante and Mancilla, 2017), the cause of the absence of associations between negative binomial distribution and aggregated pattern is due probably to complex ecological process, such as environmental heterogeneity (Elliot, 1975;Benton, Lapsley, Beckerman, 2002). This environmental heterogeneity specifically in stochastics changes in abiotic parameters, would have combined effect with biological interactions such as predator-prey interactions and migration process that can be enhanced in fragmentary habitats would explain these changes in spatial distribution patterns observed in the present study (Bull et al, 2007;De Roissart, Wang, Bonte, 2015;Deharnais, Reuman, Costantino, Cohen, 2018;Baaloudj et al, 2020;Baaloudj, De los Ríos-Escalante, Esse, 2024;Rouibi et al, 2021;Chaib et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Aegla uruguayana belongs to the Aeglidae family, which has a unique genus endemic to southern South America. This species presents benthic habits, typically sheltered at the bottom and under rocks of current rivers and streams [ 70 , 73 ], and displays strong swimming habits [ 74 , 75 ]. Its natural diet consists mainly of vegetal remains and diatoms with low importance of animal items [ 40 , 43 ].…”
Section: Methodsmentioning
confidence: 99%